2013
DOI: 10.1021/mp400024d
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Transport by the Polyspecific Organic Cation Transporters OCT1, OCT2, and OCT3

Abstract: Polyamines are ubiquitous organic cations implicated in many physiological processes. Because they are positively charged at physiological pH, carrier-mediated systems are necessary for effective membrane permeation, but the identity of specific polyamine transporter proteins in eukaryotic cells remains unclear. Polyspecific organic cation transporters (OCTs) interact with many natural and xenobiotic monovalent cations and have been reported to transport dicationic compounds, including the short polyamine putr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 62 publications
(145 reference statements)
5
75
2
Order By: Relevance
“…It has been also reported that putrescine and agmatine are taken up by human OCT2 (SLC22A2) [21], and spermidine is by mouse OCT2 [22]. In this communication, we studied the properties of putrescine, agmatine and spermidine uptake by hOCT2 in detail, and found that the active center of putrescine, agmatine and spermidine uptake are located on α-helices 9 to 12.…”
Section: Introductionmentioning
confidence: 74%
“…It has been also reported that putrescine and agmatine are taken up by human OCT2 (SLC22A2) [21], and spermidine is by mouse OCT2 [22]. In this communication, we studied the properties of putrescine, agmatine and spermidine uptake by hOCT2 in detail, and found that the active center of putrescine, agmatine and spermidine uptake are located on α-helices 9 to 12.…”
Section: Introductionmentioning
confidence: 74%
“…Sala-Rabanal et al have been reported that MPP + transport via mouse OCT1-2 and rat OCT3 was not significantly inhibited by 1 mM spermine, 26) although rat OCT1, 17) human OCT2, 18) and human/rat OCT3 19) accept spermine as a substrate or inhibitor. Among these OCTs, it has been reported that OCT3 is localized on the CSF side of choroid plexus epithelial cells in rats, and is involved in creatinine transport from the CSF to the cells.…”
Section: Resultsmentioning
confidence: 98%
“…Uptake of NE by aortic PVAT was reduced by inhibition of OCT3 with corticosterone. Thus, it could serve to remove excess NE (57), but there may be other physiological roles for OCT3 that may not involve blood pressure regulation, such as polyamine transport (60) and clearance of toxins (35). Therefore, OCT3 may be more necessary in the aortic PVAT due to its other roles versus mesenteric resistance PVAT.…”
Section: Discussionmentioning
confidence: 99%